India and Bangladesh in global finance governance: from structural conflict to embedded Liberalism in the climate finance regime - Mukherji, Rahul; Jha, Himanshu (Rethinking participation in global governance, 2022)
This chapter discusses India and Bangladesh’s emergence in the global economy in the area of climate politics. It examines two global institutions involved with climate finance: the Global Environment Facility (GEF) and the Green Climate Fund (GCF) from the standpoint of stakeholder participation in global governance. Results show that both the countries have embarked on a successful strategy of globalization. Both countries have made the transition from conflict towards an embedded liberal mode of cooperation. They are concerned about the ill-effects of climate change and both have also made the transition from structural conflict to embedded liberalism. They are actively participating in global negotiations, demanding resources as well as contributing substantially to domestically driven adjustment. Bangladesh and India are also actively contributing to global norms—India as an emerging power and Bangladesh as a leader among least developed nations.
Gesehen am 03.08.2023